anonymous
  • anonymous
Solve the following system of equations and show all work. y = −x2 + 4 y = 2x + 1
Mathematics
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
y = −x2 + 4 y = 2x + 1
anonymous
  • anonymous
hm
anonymous
  • anonymous
just need the steps

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
there are many diffrent ways to fo this but we r going to do this this way, staep 1 take x and y and put them on 1 side
anonymous
  • anonymous
step*
anonymous
  • anonymous
alright
anonymous
  • anonymous
y +x^2= 4 y - 2x = 1 then subtract y from y
anonymous
  • anonymous
i think i dont i just oearned his last month
anonymous
  • anonymous
yeah i dont no sorry
anonymous
  • anonymous
thats a hard question
anonymous
  • anonymous
1. Subtract the 2 equations and factor them out and set equal to 0 to solve for x: \[-x^2-2x+3=0\rightarrow -(x^2+2x-3)=0\rightarrow -[(x+3)(x-1)]=0\] 2. Then, solve for x: \[x = -3 and 1\] 3. Plug x in to solve for y for 1 solution: \[y = 2x+1\rightarrow y = 2(1)+1\rightarrow y = 3\] 4. Plug in x to solve y for 2nd solution: \[y = 2x + 1\rightarrow y = 2(-3)+1\rightarrow y = -5\] 5. Solutions are (1,3) and (-3,-5)

Looking for something else?

Not the answer you are looking for? Search for more explanations.